Weekly Text Messages to Support Adherence to Oral Pre-Exposure Prophylaxis (PrEP) Among Gay, Bisexual, and Other Cisgender Men Who Have Sex With Men (MSM) and Transgender Women: Pilot Randomized Controlled Trial Nested in PrEP Brasil Study - Luana Monteiro Spindola Marins; Thiago Silva Torres; Ronaldo Ismerio Moreira; Iuri Costa Leite; Marcelo Cunha; Brenda Hoagland; Lucilene Araujo Freitas; Debora Castanheira; Carolina Coutinho; Emilia Moreira Jalil; Mayara Secco Torres Silva; Jose Valdez Madruga; et al. (Journal of Medical Internet Research)
Abstract BackgroundMobile phones have become popular tools to support public health interventions (mobile health [mHealth]). Text messaging, including SMS, is a simple, low-cost approach for health communication to a large population and offers valuable tools in improving health outcomes. Despite the global advances in HIV treatment and prevention, the HIV epidemic continues to disproportionately affect certain populations such as men who have sex with men (MSM) and transgender women, including in Latin America. ObjectiveThis study aimed to evaluate the effectiveness of SMS text messaging in improving adherence after 1-year provision of oral pre-exposure prophylaxis (PrEP) among MSM and transgender women in Brazil. MethodsPilot randomized controlled trial nested in the PrEP Brasil study, a prospective, multicenter, open-label implementation study assessing PrEP delivery in the context of the Brazilian Public Health System. Those who agreed to participate in the pilot trial were randomized 1:1 to standard-of-care (SOC) or intervention (SMS text messaging) arm. SMS text messages were launched fully automated weekly to participants for 48 weeks. Adequate adherence to PrEP has been defined as having (1) tenofovir-diphosphate concentration of ≥700 fmol/punch, (2) medication possession ratio of ≥1.07, (3) pill count of ≥90.1%, and (4) self-report (structured questionnaire) of ≥99.9%. Adequate adherence outcomes at week 48 were compared between arms (SMS text messaging vs SOC) using univariate logistic regression. Comparisons were also performed for young MSM aged 18‐24 years and transgender women. ResultsFrom 450 participants enrolled on PrEP Brasil, 417 (92.7%) were randomized to the pilot trial: 210 to SOC and 207 to SMS arm. Until week 48, participants received a total of 14,099 SMS with the text message: “Are you okay?,” and 6959 (49.4%) messages were replied. Of these, the vast majority replied “Yes” (6762/6959, 97.2%). A total of 347 (83.2%) participants completed the study with no difference between arms for the 4 adherence outcomes. Conversely, young MSM who received SMS text messages had 2.50 increased odds of having adequate PrEP adherence measured by medication possession ratio (P ConclusionsSMS text messaging intervention improved adequate PrEP adherence among young MSM and can be a useful tool for PrEP coverage and persistence. Future interventions using other mHealth tools such as WhatsApp messages and apps tailored to support PrEP adherence should be evaluated among MSM and transgender women in Brazil.